Impact of Calcium Doping on the Electronic and Optical Characteristics of Strontium Hydride (SrH2): A DFT Study - Hamza Errahoui; Mohamed Karouchi; Abdelkebir Ejjabli; Aymane El haji; Abdelmounaim Laassouli; Omar Ait El Alia; Salah Chaji; Youssef Lachtioui; Omar Bajjou (Atoms)
This study investigates the electronic and optical properties of calcium-doped strontium hydride (SrH2) using first-principles density functional theory (DFT) calculations via the CASTEP code with generalized gradient approximation (GGA). We explore the impact of calcium (Ca) doping on the electronic band structure, density of states (DOS), and optical absorption spectra of SrH2. Our results show that Ca doping significantly alters the electronic properties of SrH2, notably increasing the indirect bandgap from 1.3 eV to 1.6 eV. The DOS analysis reveals new states near the Fermi level, primarily from Ca 3d orbitals. Moreover, the optical absorption spectra display enhanced absorption in the visible range, suggesting the potential for optoelectronic applications. This research highlights the feasibility of tuning the electronic and optical characteristics of SrH2 through Ca doping, thus opening the way for the generation of advanced materials with tailored properties.